Integrasi Pesantren pada Sistem Pendidikan Formal di Sekolah Dasar Negeri (SDN) - Umi Musya'adah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
This study aims to see how Islamic boarding schools apply the totality of education by relying on exemplary, environment and habituation through various tasks and activities. So that all what children see, hear, feel and do is education. In the midst of globalization, people are increasingly individualistic and materialist, so education oriented to character values ​​is needed. In this context, the pesantren has succeeded in educating its students with these character values. School is a place where students experience a process of socialization, and influence children to conform (adapt) to prevailing norms. During the first years of children entering school, the school emphasizes the importance of the control function more than other functions. therefore there should be an integration of pesantren into the formal education system in public elementary schools (SDN).